Training improves ACL outcomes in female athletes - Roniger, L. R. (2002)
Despite increasing attention from orthopedists and researchers, season-ending anterior cruciate ligament tears continue to plague female athletes, from high school soccer players to professional basketball teams. However, our understanding of what causes the injury and disposes athletes to it is growing. The use of exercise programs designed to forestall ACL mishaps is also increasing, as is evidence of the effectiveness of such programs. Additionally, newer research is examining the possibility of instituting proactive exercise programs to train girls' bodies before the teen years, when the risk of ACL injury rises substantially. Researchers continue to examine the biomechanical differences between men and women, as well as biomechanical factors associated with increased risk in either gender. Other investigations have looked at the role of menstrual cycle phase and hormones that are present in greater concentrations in women. A clear picture has not yet emerged. One of the pioneers in the field, Tim Hewett, PhD, director of the Sports Medicine Research Institute and Human Performance Laboratory at Children's Hospital Research Foundation in Cincinnati, began work on a training program for female athletes in 1993 and continues its development today. He is studying the use of tests that may determine which athletes are most at risk for ACL injury, so that they can be targeted for appropriate training. Hewett often uses a simple box drop test, during which athletes jump off a box 12 inches high, to identify risk factors such as poor muscular control of medial lateral knee motion. He is also exploring whether gender differences arise at particular developmental periods and if tackling them at that time through training programs can decrease the risk of future injuries. Other researchers have been following Hewett's lead in developing exercise programs, sometimes incorporating some of his methods. A group of practitioners and researchers who met in June 1999 in Hunt Valley, MD, to discuss the risk factors for and prevention of ACL injuries endorsed the use and further study and development of such regimens. An article in the May/June 2000 issue of the Journal of the American Academy of Orthopaedic Surgeons reported on the group's consensus. Additionally, development of exercise- and training-based programs is being influenced by ongoing research on hormonal, neuromuscular, proprioceptive, and motor control issues that may contribute to the relatively high rate of anterior cruciate ligament injury in women. "We still don't understand which components are the key ones," said Ed Wojtys, MD, a professor of surgery and director of sports medicine at the University of Michigan in Ann Arbor, regarding Hewett's program. "But it's exciting news that you could train and could improve some parameters. It's music to my ears." Getting with the exercise program After returning from the Hunt Valley gathering, Bert R. Mandelbaum, MD, an orthopedic surgeon at the Santa Monica Orthopaedic and Sports Medicine Group in California, gathered a group of physical therapists and athletic trainers to develop an exercise and training program to help female athletes avoid ACL injuries. This group focused on what it could do to most effectively prevent ACL injuries, according to Holly Silvers, MPT, ACL Prevention Program project coordinator. "We can't control hormonal issues," she said. "We focused on the biomechanical end where we can intervene." Mandelbaum's group examined Hewett's existing program and used it as a model, Silvers said. However, while the Hewett program took up to an hour to complete and was geared toward female basketball players, the Mandelbaum program, named PEP (prevent injury, enhance performance), was designed for female soccer players to perform in about 20 minutes (see table). Equipment is simple: soccer balls and cones. Players are instructed to follow the program two to three times weekly in place of a regular warm-up. "We wanted to make ours efficient and easy to use, with little equipment," Silvers said. The program focuses on learning to land correctly and softly with bent hip and knee, strengthening major muscle groups, sport-specific agility drills such as cutting and deceleration, and plyometrics, which include jumping and power drills and reinforce soft landing skills. PEP's objectives are to help athletes avoid positions in which they are vulnerable to injury, increase flexibility and strength, include plyometric exercises in their training programs, and improve proprioception. In the fall of 2000, Mandelbaum's research group distributed 20-minute videotapes outlining the program to coaches of teams in the Coast Soccer League, which is made up of more than 1000 single-sex competitive teams in Southern California, with male and female players ranging in age from nine to 19. All teams composed of female players between ages 14 and 18 were invited to participate in the group's initial study of the PEP program; 52 teams chose to do so. Coaches, managers, and players from the participating teams watched the videotape, which emphasizes ACL injury prevention, Silvers said. Over the 12-week season, two ACL tears were reported and confirmed by MRI in players on the PEP program teams, compared to 32 on the other teams. The occurrence of ACL tears was 88% lower in the PEP athletes than in the control group, according to an abstract Mandelbaum's research group plans to present in February at the AAOS meeting in Dallas. "The program is also reducing ankle and hip injuries and increasing joint awareness, not only at the knee, but at the hip and ankle," Silvers said. "We know that our program is working." A November/December 1999 study by Hewett published in the American Journal of Sports Medicine looked at ACL injuries in female high school athletes who participated in soccer, volleyball, and basketball. A group of 366 female athletes underwent Hewett's six-week training program, and two of them sustained noncontact ACL injuries during their sports season. Of another 463 female athletes in the study not trained in the program, 10 injured their anterior cruciate ligaments; eight of the injuries were due to noncontact mishaps. Additionally, the injuries of 434 male athletes (not trained in the program) were monitored, with two sustaining anterior cruciate ligament injuries, one of which was noncontact. Silvers and Mandelbaum are continuing to study the effectiveness of the PEP program in 14 to 18-year-old female Coast Soccer League players and are recruiting more teams. This fall, the research group also began working with biomechanics researchers at the University of Southern California in Los Angeles, who planned to study teams of 14-year-old female soccer players before and after PEP training. Using force plates, motion cameras, and surface EMGs, the researchers planned to measure ground reaction forces and valgus force vectors for landing and crosscutting movements, as well as a variety of hip and lower extremity muscular responses, Silvers said. Mandelbaum's research group also began a pilot study in the fall, in conjunction with statisticians at the Centers for Disease Control and Prevention in Atlanta, to look at the effectiveness of PEP in 14 Division I NCAA women's soccer teams. The PEP program may be made available to all Division I women's soccer teams this fall through a randomized study, Silvers said. The research group would also like to expand the program to basketball players and possibly other sports with relatively high ACL injury rates in women, such as volleyball, and modify the program to incorporate sport-specific agility and plyometric drills. Meanwhile, researchers at the Neuromuscular Research Laboratory at the University of Pittsburgh this year began a four-year study of ACL injuries in high school and college-level female athletes. They will examine whether a training program of their own design can help reduce the incidence of ACL injury. More than 60 high school female athletes participating in a variety of sports have already enrolled in the program, which will involve proprioceptive training, hip and knee muscle strengthening drills, reflex training, and agility drills, as well as instruction in effective landing strategies. "We believe data from this study will provide a basis for preparing female athletes for safer participation in fitness and sports activities by reducing their vulnerability to knee ligament injuries while perhaps enhancing their athletic performance," said Scott Lephart, PhD, ATC, director of the laboratory and principal investigator for the ACL study, in a written statement. High-risk profiling Hewett is continuing to teach his ACL prevention program, which focuses on incorporating proper landing form and increasing hamstring strength, to female athletes. However, he has also begun exploring strategies for identifying which athletes may be at greater risk of ACL injury. "We've been working for the past eight years on identifying the biomechanical differences between the male and female athlete," Hewett said. "Recently, we've put together a framework for what we consider to be indications of a high-risk athlete. If we want to be able to identify through screening those athletes who are at risk, we need to be able to quantify who is in the lower percentiles in various neuromuscular and biomechanical areas. Then we can develop helpful training programs." At the annual Mayo Sports Medicine Symposium in Rochester, MN, in November 2000, Hewett introduced the concept of "three-way neuromuscular imbalance" as a framework to help recognize which female athletes in jumping, cutting, or pivoting sports are at high risk for ACL injuries. Its three components are reaction force dominance, which occurs when athletes let reaction forces produced on landing or pivoting dominate instead of using the musculature around their knees to control knee torque; quadriceps dominance, in which quadriceps strength is out of proportion to hamstring strength; and dominant leg dominance, in which muscle strength and balance between legs is unequal. "One of the biggest predictors for knee ligament injuries in both men and women is side-to-side differences in hamstring strength," Hewett said. Reaction force dominance can be identified through a box drop test. "I think more valgus motion in female athletes is an indication of lack of good control of the knee joint," Hewett said. "If it has muscular stiffness, their knees may slam together, indicating a lack of good medial and lateral control." Reaction force dominance is related to quadriceps dominance, Hewett said, which is seen in female athletes who primarily use their quadriceps instead of their hamstrings when pivoting or landing from a jump. This can pull the tibia forward and increase stress on the ACL, he explained. Hewett is working on further developing a high-risk athlete profile and new training techniques. He would also like to create a database that could be used to predict the likelihood of an individual athlete's susceptibility to injury. Leaving the Cincinnati Sportsmedicine Research and Education Foundation earlier this year, Hewett took up a new position at the Children's Hospital Research Foundation with the goal of studying ACL injuries in younger athletes. "An important question is, when do these gender differences develop?" Hewett said. "We are trying to screen for these differences at earlier ages so that we can develop training programs and interventions that we may be able to use in younger and younger children, or that we can use during a relevant time period." Hewett speculated that it might be possible to teach young athletes certain skills at particular developmental periods instead of retraining at older ages, as is being done now. While a sizable gender gap exists in postpubescent knee injury incidence, Hewett is trying to find out if this gap is present beforehand and if puberty is a crucial time. "Girls mature earlier and more quickly," he said. "Neurologically, does this have an effect on development? Is it difficult for the neural system?" Hewett intends to find answers to these developmental mysteries. His work for now includes training elite athletes ranging from age seven up through college age to participate in his program and analyzing their ACL injury risk. In early September, he visited the women's basketball team at the University of Florida in Gainesville, where he had the athletes perform tests with their coaches watching. "The coaches were surprised at how poorly the players performed on these tests and how imbalanced a lot of these kids were," Hewett said. "Education is such an important aspect of this problem. If you don't know what they're doing wrong, you can't correct it." Many of the drills Hewett had the Florida players perform were sport-specific, involving jumps such as basketball lay-ups. He instructed them to think of the knee as a hinge and to use their feet as rockers when landing. He planned for the athletes to initially work on the quality of their movements, later progressing to incorporate more volume and strength training. "There really aren't a lot of preventive measures out there," said Kellye Mowchan, ATC/L, director of women's health for the University of Florida Athletic Association. "A lot of the techniques Hewett used make sense and are things we should be doing anyway." Hewett presented the results of new research, which showed physical performance changes in 11 female high school volleyball players after they took part in a six-week training program, at the National Athletic Trainers' Association conference in Los Angeles in June and the American Orthopaedic Society for Sports Medicine conference in Keystone, CO, in August. In addition to stretches, plyometrics, weight training, and jumping, the program includes neuromuscular training to learn correct posture with the chest over the knees and the knees over the balls of the feet, the ability to jump straight up without moving to the side or back and forth, and to perform soft landings rocking from the toe to midfoot. Results comparing the subjects' performances before and after training showed that peak landing forces decreased 22%, peak valgus and varus moments at the knee decreased 40% to 50%, peak jump height increased 10%, and hamstring strength increased significantly, reducing imbalances between hamstring and quadriceps strength and imbalances in hamstring strength between dominant and nondominant legs. Behind the fancy footwork While study results indicate that training programs like Hewett's and Mandelbaum's appear to be reducing ACL injury incidence in female athletes, researchers remain unsure as to why women are at increased risk for ACL tears in the first place. Wojtys has recently been researching the role of hormones. A study he presented in August at the AOSSM conference found that women were more likely than expected to experience an ACL injury while ovulating, midway through their menstrual cycle. This was reportedly the first study to determine cycle phase through actual laboratory testing, measuring estrogen, progesterone, and luteinizing hormone metabolites in the urine of 65 female athletes within 24 hours of sustaining an ACL injury and at the beginning of their next menstrual cycle. Forty-three percent of the total group participants were injured during the ovulatory phase, according to the study results, compared to an expected rate of 18%. During the luteal phase, a significantly lower rate of injury was observed: 34% compared to an expected rate of 50%. Expected rates were calculated based on the expected duration of each phase as a proportion of the menstrual cycle. Oral contraceptive use reduced the association between ACL injury and ovulatory phase, with 29% of the 14 women who used oral contraceptives becoming injured during that period. Of the women who were not using oral contraceptives, 47% sustained their injuries during the ovulatory phase, a statistically significant difference compared to the expected rate. "We don't know where the hormones are acting," Wojtys said. "We don't know which hormone, though estrogen is the most suspicious." Another study conducted by Wojtys, which has been accepted for publication by The Journal of Bone and Joint Surgery, concluded that female athletes may have less muscular protection of the knee than male athletes, which may explain some of the gender difference in ACL injury rates. Ten male and 13 female volunteers underwent arthrometer measurement of passive anterior tibial translation and a subjective evaluation of knee function and activity level. They also performed an isokinetic dynamometer strength test at 60 degrees /second and a dynamic stress test while their lower extremity muscle responses were monitored. The researchers found that while maximum cocontraction of the knee musculature decreased mean anterior tibial translation in both genders, the corresponding percentage increase in knee shear stiffness was significantly greater in male subjects, at 379%, than in female subjects, at 212%. In another study that Wojtys presented at the AOSSM conference, he determined that female athletes involved in pivoting sports volitionally increased their rotational knee stiffness significantly less than male athletes in the same sports. Twenty-four NCAA Division I athletes, evenly divided by gender, who competed in the high-risk sports of soccer, basketball, and volleyball served as subjects. These athletes were matched for age, height, weight, body mass index, shoe size, and activity level with 14 male and 14 female collegiate athletes who took part in the lower risk, nonpivoting sports of cycling, crew, and running. A device fabricated by the research team was used to test the subjects' rotational knee laxity at varying knee angles, and tibial rotation was measured at 30 degrees and 60 degrees of knee flexion, with and without maximal muscle coactivation, for all subjects. The device incorporated a bike seat that adjusted to vary knee flexion, a turntable to allow internal and external rotation of the foot around the tibia, and a weighted pendulum. Female athletes in pivoting sports showed a volitional increase in knee joint stiffness of 171%, while pivoting males were measured at 258%, nonpivoting females at 198%, and nonpivoting males at 207%. Despite such research progress, concerns about the origins of ACL injury in female athletes continue to haunt Wojtys. "Is there something in their training and conditioning that causes this?" he asked. Wojtys also speculated that the high rate of ACL injuries in females and the relative physical weaknesses seen in such athletes might be related to factors that haven't yet been addressed, such as selection of individuals who compete in ACL injury high-risk sports. "They are recipients of some of the best training and conditioning in the world," Wojtys said of the NCAA Division I female athletes who continue to incur frequent ACL injuries. "And in fact, their ACL injuries could be getting worse."